2014
DOI: 10.1016/j.ccr.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 Overexpression Drives DNA Hypomethylation and Hepatocellular Carcinoma

Abstract: SUMMARY UHRF1 is an essential regulator of DNA methylation that is highly expressed in many cancers. Here, we use transgenic zebrafish, cultured cells and human tumors to demonstrate that UHRF1 is an oncogene. UHRF1 overexpression in zebrafish hepatocytes destabilizes and delocalizes DNMT1, causes DNA hypomethylation and Tp53-mediated senescence. Hepatocellular carcinoma (HCC) emerges when senescence is bypassed. tp53 mutation both alleviates senescence and accelerates tumor onset. Human HCCs recapitulate this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
289
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 277 publications
(320 citation statements)
references
References 64 publications
16
289
3
2
Order By: Relevance
“…UHRF1 has previously been identified as an oncogene in hepatocellular carcinoma (19,20). Furthermore, the overexpression of UHRF1 destabilizes and delocalizes DNMT1, and causes DNA hypomethylation in cancer cells (19). Although several studies have demonstrated the function of UHRF1 in tumorigenesis and tumor progression (14,17,20), little is known regarding the function of UHRF1 in human osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UHRF1 has previously been identified as an oncogene in hepatocellular carcinoma (19,20). Furthermore, the overexpression of UHRF1 destabilizes and delocalizes DNMT1, and causes DNA hypomethylation in cancer cells (19). Although several studies have demonstrated the function of UHRF1 in tumorigenesis and tumor progression (14,17,20), little is known regarding the function of UHRF1 in human osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…UHRF1 is overexpressed and associated with tumor stages, and predicts poor prognosis in various types of cancer (15,21). UHRF1 has previously been identified as an oncogene in hepatocellular carcinoma (19,20). Furthermore, the overexpression of UHRF1 destabilizes and delocalizes DNMT1, and causes DNA hypomethylation in cancer cells (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary role of Uhrf1 is to recruit DNMT1 to replicating DNA where it acts to maintain methylation patterns at CpG dinucleotides through replication (28)(29)(30)(31)(32). In vertebrates, promoters with low CpG density acquire DNA methylation during development (33), which has been correlated with repression of transcriptional activity (34) and demonstrated to cause promoter silencing (35).…”
Section: Resultsmentioning
confidence: 99%
“…UHRF1 also promotes the activity, specificity and degradation of DNMT1 (Bashtrykov et al, 2014;Berkyurek et al, 2014;Qin et al, 2011). Thus, UHRF1 serves to both promote and restrict DNA methylation and, consequently, both loss (Bostick et al, 2007;Feng et al, 2010;Sharif et al, 2007) and overexpression (Mudbhary et al, 2014) of UHRF1 restructures the methylome.…”
Section: Introductionmentioning
confidence: 99%